Responding to challenges for people with psychotic illness: Updated evidence from the Survey of High Impact Psychosis. (February 2017) - Morgan, Vera A; Waterreus, Anna; Carr, Vaughan; Castle, David; Cohen, Martin; Harvey, Carol; Galletly, Cherrie; Mackinnon, Andrew; McGorry, Patrick; McGrath, John J; Neil, Amanda L; Saw, Suzy; et al.
Objective: The objective is to summarise recent findings from the 2010 Australian Survey of High Impact Psychosis (SHIP) and examine their implications for future policy and planning to improve mental health, physical health and other circumstances of people with a psychotic disorder. Methods: Survey of High Impact Psychosis collected nationally representative data on 1825 people with psychotic illness. Over 60 papers have been published covering key challenges reported by participants: financial problems, loneliness and social isolation, unemployment, poor physical health, uncontrolled symptoms of mental illness, and lack of stable, suitable housing. Findings are summarised under the rubric of participant-ranked top challenges. Results: The main income source for the majority (85%) of participants was a government benefit. Only one-third was employed, and the most appropriate employment services for this group were under-utilised. High rates of loneliness and social isolation impacted mental and physical health. The rate of cardiometabolic disease was well above the general population rate, and associated risk factors were present from a very young age. Childhood abuse (30.6%), adult violent victimisation (16.4%) and alcohol and substance abuse/dependence (lifetime rates of 50.5% and 54.5%, respectively) complicated the clinical profile. Treatment with medication was suboptimal, with physical health conditions undertreated, a high rate of psychotropic polypharmacy and underutilisation of clozapine in chronic persistent psychotic illness. Only 38.6% received evidence-based psychosocial therapies. In the previous year, 27.4% had changed housing and 12.8% had been homeless, on average for 155 days. Conclusion: Money, social engagement and employment are the most important challenges for people with psychotic illness, as well as good physical and mental health. An integrated approach to recovery is needed to optimise service delivery and augment evidence-based clinical practice with measures to improve physical health and social circumstances. Meeting these challenges has the potential to reduce costs to government and society, as well as promote recovery.